Burnout, work engagement, and resilience among Malaysian university academics. - Fairuz A Dilah Rusdi (2019)
The main purpose of this study is to investigate the relationship between burnout, work engagement, and resilience among Malaysian university academics. A mixed-methods approach was used for this study, in which a total of 681 university academics, included to represent various academic levels, completed a web-based questionnaire. In-depth interviews were also conducted (n = 12) at three-time points through the course of one semester to gain an understanding of participants’ burnout trajectories and to identify any changes to burnout levels during the academic year. All the interview data were analysed thematically. For the quantitative analysis descriptive statistics, correlation coefficients, hierarchical multiple regression, multivariate analysis of variance (MANOVA), and structural equation modelling were conducted with SPSS and Mplus. A confirmatory factor analysis (CFA) was conducted to evaluate the measurement model for resilience and burnout-engagement in university academics.